The effects of rising atmospheric carbon dioxide on shoot-root nitrogen and water signaling - Easlon, Hsien Ming; Bloom, Arnold J. (Frontiers in Plant Science, 2013)
Terrestrial higher plants are composed of roots and shoots, distinct organs that conduct complementary functions in dissimilar environments. For example, roots are responsible for acquiring water and nutrients such as inorganic nitrogen from the soil, yet shoots consume the majority of these resources. The success of such a relationship depends on excellent root-shoot communications. Increased net photosynthesis and decreased shoot nitrogen and water use at elevated CO2 fundamentally alter these source-sink relations. Lower than predicted productivity gains at elevated CO2 under nitrogen or water stress may indicate shoot-root signaling lacks plasticity to respond to rising atmospheric CO2 concentrations. The following presents recent research results on shoot-root nitrogen and water signaling, emphasizing the influence that rising atmospheric carbon dioxide levels are having on these source-sink interactions.